Assessing early warning system for flood risk reduction a case study of Barangay Tumana in Marikina City - Agyei, Vivian (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
The Philippines is ranked fourth after United States, China and India as the countries with the highest number of disasters over the past 20 years (UNODRR and CRED 2015). According to a study undertaken by the World Bank and the Philippine's national Disaster Coordinating Council, in direct damages, these hazards costs the government an average of P15bn per year, which is often more than 0.59% of the national GDP. The cost further increases if indirect and secondary impacts are considered. There is also a considerable number of social and environmental impacts associated with these disasters. Of all the disasters experienced in the Philippines, flooding is the most frequent. many dramatic flood events have been recorded since historical times. Metropolitan Manila has also been indicated as the most flood prone area in the country. Marikina City, which is one of the sixteen cities in Metropolitan Manila, is not exempted from the flooding impacts faced by the metropolis. Flooding in the city is reported to be historical with some writers linking it to the 1980s when impacts started to be felt. The city, after realizing the devastating impacts from a flood event caused by typhoon Ondoy in September 2009, decided to embark on impact reduction measures. An Early Warning System was then implemented in 2012. By considering the potential increase in impact due to climate change and non-climatic factors (such as increasing population, infrastructure), the study intends to evaluate the early warning system and provide recommendations for its improvement. The research concentrated on Barangay Tumana as a case study since it is identified by the Marikina City Disaster Risk Reduction and Management Office as the most vulnerable barangay. The researcher adopted Multi-criteria Analysis that makes use of identified parameters, criteria and weights for assessment. the identified parameters, adopted and modified from Parker and Neal (1990), Parker and Fordham (1996) included the institutional characteristics of the system, community satisfaction, and perceive reduction in flood losses (loss of lives, person injured and movable property damaged). Since there is no catalog on impacts from flooding, the reduction in flood losses was assessed based on the experience and observation of key informants and households before and after he introduction of the system. Th research identified that households are fully informed of their flooding risks and the early warning system. The warning system uses siren and sound truck as the main medium to disseminate information to households. All respondents knew they are expected to evacuate at the third warning but some refuse to leave because they ant to protect their properties from thieves. it was also identified that there was no ordinance backing the operationalization of the warning system. Nevertheless, the system is overall extremely effective. According to the perception of key informants and households, there is a significant reduction in flood losses because of the warning system. Households are also very satisfied with the time, method of dissemination and the content of the warning. To ensure sustainability, the study recommends a full institutionalization of the system with sufficient policy coverage including: ordinances, designated budget and full incorporation in city/barangay development plans to prevent negative effects from political turnover. barangay officials should coordinate with law enforcement agencies to develop a plan to protect household properties after evacuation. Finally, the main two institutions have to develop some indicators and ensure regular assessment of the system to guarantee its sustainability. To undertake effective assessment the City Disaster Risk Reduction and Management Office should develop a comprehensive catalog that includes all flood impacts.